Working with Migrant Population in Costa Rica: Reflections on the Relationship between Aid Organizations and the Foundations for Collective Action. (Revista Rupturas, 2015)
In this article we analyze the roles of migrant support organizations, and the opportunities to develop collective political action. Through the Seminars of Migration and Subjectivity at the Instituto de Investigaciones Sociales, Universidad de Costa Rica with professionals working in NGOs for migrants´ advocacy we found prioritization of care work in organizations, the struggle for external funding, and differences in approach regarding migration issues are some of the obstacles for bringing more vitality to collective political action. The efforts of some organizations tend to focus on solving immediate needs such as regularization; in the meantime, strengthening migrants as political subjects seems secondary. We propose this as the goal when working with migrant population.
Keywords: Migration; NGOs; welfarism; collective action; participatio